Facet Violation With Percutaneous Pedicle Screw Placement: Impact of 3D Navigation and Facet Orientation. Issue 3 (October 2021) - Cong, Ting; Sivaganesan, Ahilan; Mikhail, Christopher M.; Vaishnav, Avani S.; Dowdell, James; Barbera, Joseph; Kumagai, Hiroshi; Markowitz, Jonathan; Sheha, Evan; Qureshi, Sheeraz A.
Background: The gold standard for percutaneous pedicle screw placement is 2-dimensional (2D) fluoroscopy. Data are sparse on the accuracy of 3-dimensional (3D) navigation percutaneous screw placement in minimally invasive spine procedures. Objective : We sought to compare a single surgeon's percutaneous pedicle screw placement accuracy using 2D fluoroscopy versus 3D navigation, as well as to investigate the effect of facet orientation on facet violation when using 2D fluoroscopy. Methods : We conducted a retrospective radiographic study of consecutive cohort of patients who underwent percutaneous lumbar instrumentation using either 2D fluoroscopy or 3D navigation. All procedures were performed by a single surgeon at 2 academic institutions between 2011 and 2018. Radiographic measurement of screw accuracy was assessed using a postoperative computed tomographic scan. The primary outcome was facet violation, and secondary outcomes were endplate/tip breaches, the Gertzbein-Robbins classification for cortical breaches, and the Simplified Screw Accuracy grade. Statistical comparisons were made between screws placed using 2D fluoroscopy versus 3D navigation. Axial facet angles were also measured to correlate with facet violation rates. Results : In the 138 patients included, 376 screws were placed with fluoroscopy and 193 with navigation. Superior (unfused) level facet violation was higher with 2D fluoroscopy than with 3D navigation (9% vs 0.5%), which comprises the main cause for poor screw placement. Axial facet angles exceeding 45° at L4 and 60° at L5 were correlated with facet violations. Conclusion : This retrospective study found that 3D navigation is associated with lower facet violation rates in percutaneous lumbar pedicle screw placement when compared with 2D fluoroscopy. These findings suggest that 3D navigation may be of particular value when facet joints are coronally oriented.